Implementasi, Kendala dan Efektifitas Kursus Pranikah di KUA Kecamatan Pontianak Tenggara - Hakim, Muhammad Lutfi; Sugianto, Sugianto; Muala, Asyharul; Khamim, Khamim; Ismail, Habib (Institut Agama Islam Negeri Curup, 2020)
This article is aimed to explain the implementation of the premarital course, the constraints, and the effectiveness of the Regulation of Director General Bimas Islam No. DJ. II/542 Years 2013 concerning the Guidelines on the Implementation of the Premarital Course in the KUA Southeast Pontianak Sub-District. That is because KUA Southeast Pontianak Sub-District did not implement this provision optimally. The type of research the author uses is empirical legal research with a sociological-juridical approach. There are three research results in this paper. First, the premarital course in the KUA Southeast Pontianak Sub-District is held once a week. The resource person delivered four materials with the lecture and answer method, namely reproductive health, reproductive health, marital law, fostering sakīnah families, and the resilience of families. These materials are submitted by the Officers of the Health Service, Head, and the Functional Headman (Penghulu) KUA Southeast Pontianak Sub-District. After attending a premarital course, the bride candidate received a certificate from BP4. Secondly, there are two obstacles experienced by the KUA Southeast Pontianak Sub-District that have not fully implemented the Regulation of Director General Bimas Islam No. DJ. II/542 Years 2013, namely the absence of fees for the Speaker’s honorarium and yet to be present and the management of the leadership related to the implementation. Third, the guidelines for administering prenuptial courses have not been effectively implemented at KUA Southeast Pontianak Sub-District, because there are no derivative rules from these regulations (substance), the unreadiness of officials and employees in implementing them (structure), and the public’s assumption that prenuptial courses are only a formality (legal culture).